High-segment-difference filled OCA optical adhesive, preparation method and adhesive tape

Through the combination of low molecular weight acrylic resin and high molecular weight acrylic resin and the use of functional monomers, the problem of insufficient OCA optical adhesive segment difference filling performance in blind-hole screen mobile phones is solved, high-segment filling and stability are achieved, and the process is simplified. Reduced costs.

CN119286436APending Publication Date: 2025-01-10江苏晶华新材料科技有限公司
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411521840.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing fully-fit OCA optical glue has insufficient segment difference filling performance in blind-hole screen mobile phones, and the preparation process is complex and unstable, which cannot meet the high display effect requirements of blind-hole screens.

Method used

Using a combination of low-molecular-weight acrylic resin and high-molecular-weight acrylic resin, combined with functional monomers, polar groups such as hydroxyl and amide groups are introduced, and high-stage difference-filled OCA optical glue is prepared by controlling the reaction conditions to ensure its fluidity and cohesion, and simplify the process. and improve stability.

Benefits of technology

It realizes the 100% segment difference filling capacity and stability of OCA optical adhesive, reduces production costs, is suitable for room temperature transportation and die cutting, and improves the display effect of blind hole screen mobile phones.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286436A_ABST
    Figure CN119286436A_ABST
Patent Text Reader

Abstract

The invention discloses a high-segment-difference filled OCA optical adhesive and an adhesive tape preparation method. The high-segment-difference filled OCA optical adhesive comprises the following components in parts by mass: 100 parts of (methyl) acrylic resin, 0.1-1 part of a photoinitiator, 0.2-2 parts of a silane coupling agent, 0.1-1 part of an antioxidant and 0-35 parts of a solvent. The (methyl) acrylic resin comprises a (methyl) acrylic resin polymer A with the weight-average molecular weight of 1-2 million and a (methyl) acrylic resin polymer B with the weight-average molecular weight of 5-30 million; in the (methyl) acrylic resin, the mass fraction of the (methyl) acrylic resin polymer A is 10-40%, and the mass fraction of the (methyl) acrylic resin polymer B is 60-90%. The high-segment-difference filling OCA optical cement is excellent in segment-difference filling capacity, 100% filling can be achieved for common perforated polarizers in the market, and the high-segment-difference filling OCA optical cement has wide application space under the trend of OCA optical cement thinning.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of OCA optical adhesives, and in particular relates to high-step-difference-filled OCA optical adhesives, a preparation method and an adhesive tape. Background Art

[0002] In today's increasingly developed information age, mobile phones, tablets and other electronic devices have become indispensable tools in people's lives. For mobile phones, consumers are pursuing performance while also having higher and higher requirements for appearance. Mobile phone manufacturers are also increasing the screen-to-body ratio and reducing the thickness of the body to attract consumers, especially young consumer groups. Therefore, full-screen mobile phones came into being.

[0003] At present, the mainstream solutions for full-screen phones can be divided into bangs screen or water drop screen, hole screen or drilled screen, lifting screen or sliding screen, front and back dual screens. As a type of hole screen, blind hole screen has become the mainstream solution for LCD full-screen mobile phones. However, there are also some technical difficulties in the design of blind hole screens. Since the upper polarizer of the blind hole screen needs to be punched, the aperture is about 4mm and the depth is generally between 69-84μm. In order to achieve a better display effect, this hole needs to be filled. The general full-fit OCA optical glue has a step difference capacity of about 30%, which obviously cannot meet this demand. In recent years, many domestic and foreign manufacturers have developed full-fit OCA optical glue for blind hole screen mobile phones, but the step difference filling performance can only reach about 70%, and in the process of preparing OCA optical glue, the grafting monomer is mostly used to achieve post-curing requirements, which is complex and unstable.

[0004] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention

[0005] The purpose of the present invention is to provide a high-step-difference filled OCA optical adhesive, a preparation method and an adhesive tape, and a high-step-difference filled OCA optical adhesive.

[0006] In order to achieve the above object, a technical solution provided by a specific embodiment of the present invention is as follows:

[0007] A high-step-difference-filled OCA optical adhesive comprises the following components by weight: 100 parts of (meth)acrylic resin, 0.1 to 1 part of photoinitiator, 0.2 to 2 parts of silane coupling agent, 0.1 to 1 part of antioxidant, and 0 to 35 parts of solvent;

[0008] The (meth)acrylic resin includes a (meth)acrylic resin polymer A having a weight average molecular weight of 1 to 2 million and a (meth)acrylic resin polymer B having a weight average molecular weight of 50,000 to 300,000.

[0009] In the (meth)acrylic resin, the mass fraction of the (meth)acrylic resin polymer A is 10 to 40%, and the mass fraction of the (meth)acrylic resin polymer B is 60 to 90%.

[0010] In one or more embodiments of the present invention, the (meth)acrylic resin raw material includes 40 to 80 parts by mass of a soft monomer, 10 to 30 parts by mass of a hard monomer, 5 to 25 parts by mass of a functional monomer, 0.05 to 2 parts by mass of an initiator, 0 to 200 parts by mass of a solvent, and 0.01 to 1 part by mass of a molecular weight regulator.

[0011] In one or more embodiments of the present invention, the soft monomer is selected from one or more of 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, n-decyl (meth)acrylate, n-butyl (meth)acrylate, ethyl (meth)acrylate, isobutyl (meth)acrylate, propyl (meth)acrylate and lauryl (meth)acrylate.

[0012] In one or more embodiments of the present invention, the hard monomer is selected from one or more of methyl (meth)acrylate, isobornyl (meth)acrylate and cyclohexyl (meth)acrylate.

[0013] In one or more embodiments of the present invention, the functional monomer contains one or more of -COOH, -OH, amide group, or unsaturated double bond group that can participate in the curing reaction.

[0014] In one or more embodiments of the present invention, the functional monomer is selected from one or more of hydroxyethyl (meth)acrylate, hydroxybutyl (meth)acrylate, acrylamide, N-vinyl caprolactam, acrylonitrile, N-vinyl pyrrolidone, (meth)acrylic acid, 2-carboxyethyl acrylate and 4-hydroxyvinyloxybenzophenone methacrylate.

[0015] In one or more embodiments of the present invention, the molecular weight regulator is selected from one or more of n-dodecyl mercaptan, tert-dodecyl mercaptan, isooctyl trimercaptopropionate, n-octyl mercaptan and n-decyl mercaptan.

[0016] Another specific embodiment of the present invention provides a technical solution as follows:

[0017] A method for preparing a high-step-difference filled OCA optical adhesive comprises the following steps:

[0018] The (meth) acrylic resin, the photoinitiator, the silane coupling agent, the antioxidant and the solvent are mixed, stirred and degassed to obtain the high step-difference filled OCA optical adhesive.

[0019] In one or more embodiments of the present invention, the (meth)acrylic resin is prepared as follows:

[0020] In an inert gas atmosphere, add soft monomer, hard monomer, functional monomer and part of the initiator into the reactor, control the reaction temperature at 65-75°C, and keep it warm for 1.5-2.5h;

[0021] Add solvent, molecular weight regulator and part of initiator to the reactor, control the reaction temperature to 60-70°C, and keep warm for 3.5-4.5h;

[0022] Then, the remaining initiator is added, the reaction temperature is controlled at 75-82°C, and the temperature is kept at 2.5-3.5 hours to obtain (meth) acrylic resin.

[0023] Another specific embodiment of the present invention provides a technical solution as follows:

[0024] A tape comprises a heavy release film, an optical adhesive layer and a light release film which are stacked in sequence, wherein the optical adhesive layer is formed by the above-mentioned high-step-difference-filled OCA optical adhesive or the high-step-difference-filled OCA optical adhesive prepared by the above-mentioned preparation method of the high-step-difference-filled OCA optical adhesive.

[0025] Compared with the prior art, the present invention ensures the fluidity of OCA optical adhesive by introducing a large amount of low molecular weight acrylic resin, so that OCA optical adhesive can achieve 100% step filling. In addition, by adding a small amount of high molecular weight acrylic resin and introducing polar groups such as hydroxyl groups and amide groups through functional monomers, the cohesion of OCA optical adhesive is improved, so that OCA optical adhesive has higher stability, can be transported and die-cut at room temperature, and the production cost is reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1 It is a schematic diagram of the structure of the adhesive tape in one embodiment of the present invention;

[0028] Figure 2 This is a test structure diagram of the aging test in the present invention.

[0029] Description of main reference numerals:

[0030] 1. Optical adhesive layer; 2. Heavy release film; 3. Light release film; 4. POL; 5. Glass plate. DETAILED DESCRIPTION

[0031] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0032] A specific embodiment of the present invention provides a high-step-difference filled OCA optical adhesive, comprising the following components by weight: 100 parts of (meth)acrylic resin, 0.1 to 1 parts of photoinitiator, 0.2 to 2 parts of silane coupling agent, 0.1 to 1 parts of antioxidant, and 0 to 35 parts of solvent;

[0033] The (meth)acrylic resin includes a (meth)acrylic resin polymer A having a weight average molecular weight of 1 to 2 million and a (meth)acrylic resin polymer B having a weight average molecular weight of 50,000 to 300,000.

[0034] In the (meth)acrylic resin, the mass fraction of the (meth)acrylic resin polymer A is 10 to 40%, and the mass fraction of the (meth)acrylic resin polymer B is 60 to 90%.

[0035] Specifically, by controlling the content of high molecular weight acrylic resin and low molecular weight acrylic resin in OCA optical glue, a large amount of low molecular weight acrylic resin is used to ensure that the OCA optical glue has better fluidity and higher step filling ability. At the same time, a small amount of high molecular weight acrylic resin is used to ensure that the OCA optical glue has higher cohesion, so that it can maintain structural and functional stability and have excellent performance.

[0036] Preferably, in the (meth)acrylic resin, the mass fraction of the (meth)acrylic resin polymer B is 80 to 90%.

[0037] More preferably, in the (meth)acrylic resin, the mass fraction of the (meth)acrylic resin polymer A is 15 to 25%.

[0038] Preferably, the weight average molecular weight of (meth)acrylic resin polymer A is 1.2 to 1.8 million, and the weight average molecular weight of (meth)acrylic resin polymer B is 50,000 to 300,000; more preferably, the weight average molecular weight of (meth)acrylic resin polymer A is 1.4 to 1.6 million; and the weight average molecular weight of (meth)acrylic resin polymer B is 100,000 to 150,000.

[0039] Specifically, by further optimizing the weight average molecular weight of (meth)acrylic resin polymer A and (meth)acrylic resin polymer B and their content in (meth)acrylic resin, the OCA optical adhesive has better step-filling ability and performance.

[0040] In a specific embodiment, the (meth)acrylic resin raw material includes 40-80 parts by mass of soft monomer, 10-30 parts by mass of hard monomer, 5-25 parts by mass of functional monomer, 0.05-2 parts by mass of initiator, 0-200 parts by mass of solvent and 0.01-1 part by mass of molecular weight regulator.

[0041] In a specific embodiment, the soft monomer is selected from one or more of 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, n-decyl (meth)acrylate, n-butyl (meth)acrylate, ethyl (meth)acrylate, isobutyl (meth)acrylate, propyl (meth)acrylate and lauryl (meth)acrylate.

[0042] Specifically, the selection of the above types of soft monomers can better improve the flexibility and film-forming properties of (meth)acrylic resins, and can also improve the fluidity and wettability of (meth)acrylic resins, which helps to improve the step-filling ability of OCA optical adhesives.

[0043] In a specific embodiment, the hard monomer is selected from one or more of methyl (meth)acrylate, isobornyl (meth)acrylate and cyclohexyl (meth)acrylate.

[0044] Specifically, the selection of the above types of hard monomers helps to improve the hardness, solvent resistance and chemical resistance of the (meth)acrylic resin, thereby improving the weather resistance of the OCA optical adhesive.

[0045] In a specific embodiment, the functional monomer carries one or more of -COOH, -OH, amide group, or unsaturated double bond group that can participate in the curing reaction.

[0046] Specifically, by adding functional monomers, active groups such as hydroxyl groups and amide groups can be introduced to enable them to participate in the copolymerization reaction, thereby adding new cross-linking points, which helps to improve the cohesion of the OCA optical adhesive and ensure its high stability.

[0047] In a specific embodiment, the solvent is selected from one or more of ethyl acetate, toluene, isopropanol, methanol and butanone.

[0048] In a specific embodiment, the molecular weight regulator is selected from one or more of n-dodecyl mercaptan, tert-dodecyl mercaptan, isooctyl trimercaptopropionate, n-octyl mercaptan and n-decyl mercaptan.

[0049] Specifically, the molecular weight distribution of the (meth)acrylic resin can be adjusted by adding a proper amount of molecular weight regulator, thereby improving the fluidity and adhesion of the OCA optical adhesive, making it exhibit better step filling ability and stability.

[0050] Another specific embodiment of the present invention provides a method for preparing a high-step-difference filled OCA optical adhesive, comprising the following steps:

[0051] The (meth) acrylic resin, the photoinitiator, the silane coupling agent, the antioxidant and the solvent are mixed, stirred and degassed to obtain the high step-difference filled OCA optical adhesive.

[0052] In one specific embodiment, the (meth)acrylic resin is prepared as follows:

[0053] In a nitrogen atmosphere, add soft monomer, hard monomer, functional monomer and part of initiator into the reactor, control the reaction temperature at 65-75°C, and keep it warm for 1.5-2.5h;

[0054] Add solvent, molecular weight regulator and part of initiator to the reactor, control the reaction temperature to 60-70°C, and keep warm for 3.5-4.5h;

[0055] Then, the remaining initiator is added, the reaction temperature is controlled at 75-82°C, and the temperature is kept at 2.5-3.5 hours to obtain (meth) acrylic resin.

[0056] Another specific embodiment of the present invention provides an adhesive tape, such as Figure 1 As shown, it comprises a heavy release film 2, an optical adhesive layer 1 and a light release film 3 which are stacked in sequence, and the optical adhesive layer 1 is formed by the above-mentioned high-step-difference filled OCA optical adhesive.

[0057] Specifically, the heavy release film 2 has a release force of 25-40 g / 25 mm and a thickness of 70-90 μm, the light release film 3 has a release force of 5-10 g / 25 mm and a thickness of 40-60 μm, and the release film is made of PET.

[0058] The present invention is further described in detail below in conjunction with specific embodiments.

[0059] Example 1

[0060] In a 2L glass reaction device consisting of a thermometer, a stirrer, a condenser and a water bath, 60 parts of 2-ethylhexyl acrylate, 20 parts of isobornyl acrylate, 15 parts of hydroxyethyl acrylate, 2 parts of N-vinyl pyrrolidone and 3 parts of 4-hydroxyvinyloxybenzophenone methacrylate were added in parts by mass under a nitrogen atmosphere, the reaction temperature was controlled at 70°C, and 0.001 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) was added and kept warm for 2h; 150 parts of ethyl acetate and 0.2 parts of n-dodecyl mercaptan were added, the reaction temperature was controlled at 65°C, and 0.15 parts of azobisisobutyronitrile were added and kept warm for 4h; 0.3 parts of azobisisobutyronitrile were added, the reaction temperature was controlled at 79°C, and kept warm for 3h, and the (meth)acrylic resin was obtained.

[0061] Take 100 parts of (meth) acrylic resin, 0.15 parts of 1-hydroxycyclohexyl phenyl ketone, 0.2 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, 0.3 parts of 3-(2,3-epoxypropoxy)propyltrimethoxysilane and 5 parts of ethyl acetate, stir for 20 minutes to mix, and remove bubbles in vacuum to obtain high step-difference filling OCA optical adhesive.

[0062] The high-step-difference-filled OCA optical adhesive is coated on a PET film with a release force of 30g / 25mm and a thickness of 75μm, and baked at 100°C for 5 minutes. A layer of PET film with a release force of 5g / 25mm and a thickness of 50μm is applied on the high-step-difference-filled OCA optical adhesive to obtain a tape with a thickness of 225μm.

[0063] Example 2

[0064] The only difference between this embodiment and embodiment 1 is that the amount of 2,2'-azobis(2,4-dimethylvaleronitrile) used is 0.0005 parts by mass.

[0065] Example 3

[0066] The only difference between this embodiment and embodiment 1 is that the amount of 2,2'-azobis(2,4-dimethylvaleronitrile) used is 0.002 parts by mass.

[0067] Example 4

[0068] The only difference between this embodiment and embodiment 1 is that n-dodecyl mercaptan is not added.

[0069] Example 5

[0070] The only difference between this embodiment and embodiment 1 is that the amount of n-dodecyl mercaptan used is 0.5 parts by mass.

[0071] Example 6

[0072] The only difference between this embodiment and embodiment 1 is that 2-ethylhexyl acrylate is replaced by n-butyl acrylate.

[0073] Example 7

[0074] The only difference between this embodiment and embodiment 1 is that isoborneol acrylate is replaced by methyl methacrylate.

[0075] Example 8

[0076] The only difference between this embodiment and embodiment 1 is that hydroxyethyl acrylate is replaced by hydroxybutyl acrylate.

[0077] Example 9

[0078] The only difference between this embodiment and embodiment 1 is that N-vinyl pyrrolidone is replaced by acrylamide.

[0079] Comparative Example 1

[0080] In a 2L glass reaction device consisting of a thermometer, a stirrer, a condenser and a water bath, 63 parts of 2-ethylhexyl acrylate, 20 parts of isobornyl acrylate, 15 parts of hydroxyethyl acrylate, 2 parts of N-vinyl pyrrolidone and 150 parts of ethyl acetate were added in parts by mass under a nitrogen atmosphere, the reaction temperature was controlled at 70°C, and 0.001 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) was added, and the mixture was kept warm for 2 hours; 150 parts of ethyl acetate and 0.2 parts of n-dodecyl mercaptan were added, the reaction temperature was controlled at 65°C, and 0.15 parts of azobisisobutyronitrile were added, and the mixture was kept warm for 4 hours; 0.3 parts of azobisisobutyronitrile was added, the reaction temperature was controlled at 79°C, and the mixture was kept warm for 3 hours, and the (meth)acrylic resin was obtained.

[0081] To the obtained (meth) acrylic resin, 0.5 parts of ethyl isocyanate acrylate and 0.2 parts of dibutyltin dilaurate were added, by mass, and the mixture was reacted at 50° C. for 2 hours to obtain a high-step-difference filled OCA optical adhesive.

[0082] The high-step-difference-filled OCA optical adhesive was coated on a PET film with a release force of 30 g / cm and a thickness of 75 μm, and baked at 100°C for 5 minutes. A layer of PET film with a release force of 5 g / cm and a thickness of 50 μm was applied on the high-step-difference-filled OCA optical adhesive to obtain a tape with a thickness of 225 μm.

[0083] Comparative Example 2

[0084] In a 2L glass reaction device consisting of a thermometer, a stirrer, a condenser and a water bath, 60 parts of 2-ethylhexyl acrylate, 20 parts of isobornyl acrylate, 15 parts of hydroxyethyl acrylate, 2 parts of N-vinyl pyrrolidone, 3 parts of 4-hydroxyvinyloxybenzophenone methacrylate, 0.2 parts of n-dodecyl mercaptan and 150 parts of ethyl acetate were added in parts by mass under a nitrogen atmosphere, and nitrogen was replaced at a flow rate of 0.5L / min for 30min at room temperature, the temperature was raised to 65°C, 0.15 parts of azobisisobutyronitrile were added, and the mixture was kept warm for 4h, and then 0.3 parts of azobisisobutyronitrile were added, the temperature was raised to 79°C, and the mixture was kept warm for 3h, and the temperature was lowered to obtain (meth) acrylic resin.

[0085] Take 100 parts of (meth) acrylic resin, 0.15 parts of 1-hydroxycyclohexyl phenyl ketone, 0.2 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, 0.3 parts of 3-(2,3-epoxypropoxy)propyltrimethoxysilane and 5 parts of ethyl acetate, stir for 20 minutes to mix, and remove bubbles in vacuum to obtain high step-difference filling OCA optical adhesive.

[0086] The high-step-difference-filled OCA optical adhesive was coated on a PET film with a release force of 30 g / cm and a thickness of 75 μm, and baked at 100°C for 5 minutes. A layer of PET film with a release force of 5 g / cm and a thickness of 50 μm was applied on the high-step-difference-filled OCA optical adhesive to obtain a tape with a thickness of 225 μm.

[0087] Comparative Example 3

[0088] In a 2L glass reaction device consisting of a thermometer, a stirrer, a condenser and a water bath, 60 parts of 2-ethylhexyl acrylate, 20 parts of isobornyl acrylate, 15 parts of hydroxyethyl acrylate, 2 parts of N-vinyl pyrrolidone, 3 parts of 4-hydroxyvinyloxybenzophenone methacrylate and 100 parts of ethyl acetate were added in parts by mass under a nitrogen atmosphere, and nitrogen was replaced at a flow rate of 0.5L / min for 30min at room temperature, the temperature was raised to 65°C, 0.15 parts of azobisisobutyronitrile were added, and the mixture was kept warm for 4h, 0.3 parts of azobisisobutyronitrile were added, the temperature was raised to 79°C, and the mixture was kept warm for 3h, and the temperature was lowered and discharged to obtain (meth) acrylic resin.

[0089] Take 100 parts of (meth) acrylic resin, 0.15 parts of 1-hydroxycyclohexyl phenyl ketone, 0.2 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, 0.3 parts of 3-(2,3-epoxypropoxy)propyltrimethoxysilane and 5 parts of ethyl acetate, stir for 20 minutes to mix, and remove bubbles in vacuum to obtain high step-difference filling OCA optical adhesive.

[0090] The high-step-difference-filled OCA optical adhesive was coated on a PET film with a release force of 30 g / cm and a thickness of 75 μm, and baked at 100°C for 5 minutes. A layer of PET film with a release force of 5 g / cm and a thickness of 50 μm was applied on the high-step-difference-filled OCA optical adhesive to obtain a tape with a thickness of 225 μm.

[0091] The manufacturers of raw materials used in the present invention are shown in Table 1:

[0092] Table 1 Raw materials corresponding manufacturers

[0093]

[0094]

[0095] The following performance tests were performed on the high-step-difference-filled OCA optical adhesives prepared in each embodiment and each comparative example:

[0096] 180° peel adhesion test: Tested according to ASTM D3330, temperature conditions: temperature 23°C, humidity 65% ​​RH, test substrate SUS A board: sample width 25mm, speed 300mm / min.

[0097] Optical performance test: Tested using Konica Minolta colorimetric system, model CM-36dG.

[0098] Dynamic thermomechanical analysis: According to ASTM D4440-15, the test was carried out using Anton Paar rheometer MCR 102e.

[0099] Molecular weight and molecular weight distribution test: refer to GB / T 21863-2008, and use gel permeation chromatograph Agilent 1260 Infinity for testing.

[0100] Glass transition temperature test: refer to GB / T 19466.2-2004, use differential scanning calorimeter TA Q2000 for testing.

[0101] Table 2 Performance test results

[0102]

[0103] It can be seen from Table 2 that compared with the method of introducing cross-linking groups by grafting in Comparative Example 1, the embodiment of the present invention can also obtain OCA optical adhesive with high step-difference filling performance by directly adding functional monomers to introduce cross-linking groups during the preparation process, and the preparation method of the present invention is simpler and has a higher fault tolerance.

[0104] Compared with Comparative Examples 2 and 3, the embodiments of the present invention can improve the loss factor tanδ of the OCA optical adhesive, especially the loss factor in the high temperature section, by combining a low molecular weight (meth) acrylic resin polymer and a high molecular weight (meth) acrylic resin polymer and controlling their respective proportions. As shown in Table 2, the loss factor at 60°C reaches above 1.0, and the OCA optical adhesive at this time exhibits better flow properties, which is conducive to step filling. Moreover, the introduction of high molecular weight (meth) acrylic resin polymers and the introduction of polar groups through functional monomers enhance the intermolecular forces of the OCA optical adhesive, such as hydrogen bonds and van der Waals forces, so that the OCA optical adhesive can maintain stability at room temperature, which is conducive to the transportation and die-cutting of the OCA optical adhesive.

[0105] Take the adhesive tape in Example 1, use CEF 7104 adhesive as comparative example 4, use Mitsubishi G9.2 adhesive as comparative example 5, and use SLC 6010 adhesive as comparative example 6 for aging test. Specifically: Figure 2 As shown in the test structure, take two clean glass plates, apply OCA optical glue and POL (polarizer) respectively. POL is a perforated type with a thickness of 69-89μm. Remove the release film of OCA optical glue and the protective film of POL respectively, use a laminating machine to laminate, and then degas (temperature 50℃, pressure 0.6MPa, time 45min), UV curing (high-pressure mercury lamp curing, energy 2000mJ), and then put into the corresponding aging equipment. Take out after a certain period of time, observe the appearance, and record the yield.

[0106] Table 3 Lamination aging test results

[0107]

[0108] Note: In Table 3, OK represents a yield of 100%, and NG represents a yield of 0%.

[0109] As can be seen from Table 3, Comparative Examples 4 to 6 are commercially available OCA optical adhesives, which have better effects when bonding relatively thin (69 μm) POLs, but poor performance when bonding thicker POLs. For example, when bonding 84 μm POLs, the degassing yield of Comparative Example 4 is only 10%, and Comparative Examples 5 and 6 are all NG. However, the OCA optical adhesive in Example 1 of the present invention has excellent effects when bonding POLs of different thicknesses, and the test results are all OK in the aging test.

[0110] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0111] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A high-step-difference-filled OCA optical adhesive, characterized in that: The invention comprises the following components by weight: 100 parts of (meth) acrylic resin, 0.1 to 1 parts of photoinitiator, 0.2 to 2 parts of silane coupling agent, 0.1 to 1 parts of antioxidant, and 0 to 35 parts of solvent; The (meth)acrylic resin includes a (meth)acrylic resin polymer A having a weight average molecular weight of 1 to 2 million and a (meth)acrylic resin polymer B having a weight average molecular weight of 50,000 to 300,000. In the (meth)acrylic resin, the mass fraction of the (meth)acrylic resin polymer A is 10 to 40%, and the mass fraction of the (meth)acrylic resin polymer B is 60 to 90%.

2. The high-step-difference-filled OCA optical adhesive according to claim 1, characterized in that: The (meth) acrylic resin raw material comprises 40-80 parts by weight of soft monomer, 10-30 parts by weight of hard monomer, 5-25 parts by weight of functional monomer, 0.05-2 parts by weight of initiator, 0-200 parts by weight of solvent and 0.01-1 part by weight of molecular weight regulator.

3. The high-step-difference-filled OCA optical adhesive according to claim 2, characterized in that: The soft monomer is selected from one or more of 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, n-decyl (meth)acrylate, n-butyl (meth)acrylate, ethyl (meth)acrylate, isobutyl (meth)acrylate, propyl (meth)acrylate and lauryl (meth)acrylate.

4. The high-step-difference-filled OCA optical adhesive according to claim 2, characterized in that: The hard monomer is selected from one or more of methyl (meth)acrylate, isobornyl (meth)acrylate and cyclohexyl (meth)acrylate.

5. The high-step-difference-filled OCA optical adhesive according to claim 2, characterized in that: The functional monomer contains one or more of -COOH, -OH, amide group, or unsaturated double bond group that can participate in the curing reaction.

6. The high-step-difference-filled OCA optical adhesive according to claim 5, characterized in that: The functional monomer is selected from one or more of hydroxyethyl (meth)acrylate, hydroxybutyl (meth)acrylate, acrylamide, N-vinyl caprolactam, acrylonitrile, N-vinyl pyrrolidone, (meth)acrylic acid, 2-carboxyethyl acrylate and 4-hydroxyvinyloxybenzophenone methacrylate.

7. The high-step-difference-filled OCA optical adhesive according to claim 2, characterized in that: The molecular weight regulator is selected from one or more of n-dodecyl mercaptan, tert-dodecyl mercaptan, isooctyl trimercaptopropionate, n-octyl mercaptan and n-decyl mercaptan.

8. A method for preparing the high-step-difference filled OCA optical adhesive according to any one of claims 1 to 7, characterized in that: The following steps are involved: The (meth) acrylic resin, the photoinitiator, the silane coupling agent, the antioxidant and the solvent are mixed, stirred and degassed to obtain the high step-difference filled OCA optical adhesive.

9. The method for preparing the high-step-difference filled OCA optical adhesive according to claim 8, characterized in that: The preparation of (meth) acrylic resin is: In an inert gas atmosphere, add soft monomer, hard monomer, functional monomer and part of the initiator into the reactor, control the reaction temperature at 65-75°C, and keep it warm for 1.5-2.5h; Add solvent, molecular weight regulator and part of initiator to the reactor, control the reaction temperature to 60-70°C, and keep warm for 3.5-4.5h; Then, the remaining initiator is added, the reaction temperature is controlled at 75-82°C, and the temperature is kept at 2.5-3.5 hours to obtain (meth) acrylic resin.

10. An adhesive tape, characterized in that: It comprises a heavy release film, an optical adhesive layer and a light release film which are stacked in sequence, wherein the optical adhesive layer is formed by the high-step-difference-filled OCA optical adhesive described in any one of claims 1 to 7 or the high-step-difference-filled OCA optical adhesive prepared by the preparation method of the high-step-difference-filled OCA optical adhesive described in any one of claims 8 to 9.

Citation Information

Cited By

  • Optical optical clear adhesive (OCA) with high flexibility and high adhesion and preparation method thereof

    CN120484703A